Tools for measuring individual self-care capability: a scoping review - Austen El-Osta; Eva Riboli Sasco; Evelina Barbanti; Iman Webber; Aos Alaa; Manisha Karki; Marie line El Asmar; Haitham Idriss; Mashael Almadi; Farah Massoud; Ahmed Alboksmaty; Azeem Majeed (BMC, 2023)
Abstract Background Our ability to self-care can play a crucial role in the prevention, management and rehabilitation of diverse conditions, including chronic non-communicable diseases. Various tools have been developed to support the measurement of self-care capabilities of healthy individuals, those experiencing everyday self-limiting conditions, or one or more multiple long-term conditions. We sought to characterise the various non-mono-disease specific self-care measurement tools for adults as such a review was lacking. Objective The aim of the review was to identify and characterise the various non-mono-disease specific self-care measurement tools for adults. Secondary objectives were to characterise these tools in terms of their content, structure and psychometric properties. Design Scoping review with content assessment. Methods The search was conducted in Embase, PubMed, PsycINFO and CINAHL databases using a variety of MeSH terms and keywords covering 1 January 1950 to 30 November 2022. Inclusion criteria included tools assessing health literacy, capability and/or performance of general health self-care practices and targeting adults. We excluded tools targeting self-care in the context of disease management only or indicated to a specific medical setting or theme. We used the Seven Pillars of Self-Care framework to inform the qualitative content assessment of each tool. Results We screened 26,304 reports to identify 38 relevant tools which were described in 42 primary reference studies. Descriptive analysis highlighted a temporal shift in the overall emphasis from rehabilitation-focused to prevention-focused tools. The intended method of administration also transitioned from observe-and-interview style methods to the utilisation of self-reporting tools. Only five tools incorporated questions relevant to the seven pillars of self-care. Conclusions Various tools exist to measure individual self-care capability, but few consider assessing capability against all seven pillars of self-care. There is a need to develop a comprehensive, validated tool and easily accessible tool to measure individual self-care capability including the assessment of a wide range of self-care practices. Such a tool could be used to inform targeted health and social care interventions.